Analysis of the Effect of Service Quality on Loyalty in Banking Customers - Cuandra, Fendy; Wijaya, Calvin; Candy, Candy (Politeknik Negeri Bengkalis, 2024)
This research aims to understand the impact of service quality, trust, brand image, brand awareness, and CSR (Corporate Social Responsibility) on customer loyalty, with customer satisfaction as an intervening variable in conventional banks. This research is grouped as causal-comparative research. This study targets Batam conventional banks as the subject. Purposive sampling is used to select samples, and the selected samples must meet certain requirements. Bank Rakyat Indonesia, Bank Central Asia, and Bank Negara Indonesia were chosen as samples because they were recipients of the title